Analisis Elemen Visual Pada Poster Film Miracle In Cell No.7 - Fitriani, Dian; Asril; N, Sahrul (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
A film poster is the identity of a film which functions as a promotional medium for the film. Promotion of the film Miracle in Cell No.7 by Hanung Bramantyo uses internet marketing techniques, by uploading film posters to social media. This research aims to analyze the various meanings of the signs implied in the film poster Miracle in Cell No.7. This research is qualitative research, the data analysis method consists of four stages of design review, namely, work description, formal analysis, interpretation, and evaluation. The work description describes all the elements contained in the film poster Miracle in Cell No.7. Formal analysis is technically discussing how basic elements such as illustrations, colors, and typography are arranged to form a single unit in an order or layout. Interpretation is interpreting the meaning of signs based on Charles Sanders Pierce's semiotic theory which includes icons, indices, and symbols. Evaluation is outlining the conclusions of all the stages that have been passed. The research results found that various signs were in harmony with each other so that they supported the message conveyed in the film poster. It was concluded that the visualization of the main illustrations, supporting visuals, colors, and typography displayed on the visual poster for the film Miracle in Cell No.7 gives an implied picture of a father's love for his daughter, until one day they had to separate because justice was not on his side